VOP (Encyclopedia of Pain, 2006)
Objective To characterize the signalment and clinical presentation of glaucoma in pet rabbits. Animal studied Client-owned pet rabbits (n = 222) referred to an exotic specialty animal hospital for ophthalmic examination between 2007 and 2023. Procedure Medical records were retrospectively reviewed for rabbits diagnosed with glaucoma, to evaluate clinical findings and treatments. In addition to routine ophthalmic examination, gonioscopy and Encephalitozoon cuniculi serologic testing were performed when indicated. Results Of 222 rabbits examined, 63 (28.4%) were diagnosed with glaucoma of which 33/63 (52.4%) were categorized as primary glaucoma and 27/63 (42.9%) as secondary glaucoma. Three other rabbits (4.8%) presented with unilateral secondary glaucoma with primary glaucoma risk in the fellow eye (mixed-risk glaucoma). The mean age at diagnosis was 4.4 ± 2.8 years for primary and 10.0 ± 5.3 years for secondary glaucomas. Gonioscopy was performed in 23/33 (69.7%) of rabbits in the primary glaucoma group revealing a closed iridocorneal angle in 16/23 (69.6%). Median follow-up was 707 days [IQR 126-1299] for primary and 59 days [IQR 1-1623] for secondary glaucomas. Medical management involved various topical antiglaucoma medications, with treatment regimens adjusted and often progressing to multi-drug therapy. Bilateral glaucoma was ultimately documented in 75.8% (25/33) of primary and 29.6% (8/27) of secondary glaucomas. The most common underlying ocular condition associated with secondary glaucoma was suspected to be E. cuniculi infection. Conclusions Both primary and secondary glaucomas are prevalent among pet rabbits in the Japanese population. Further studies are needed into the possible genetic factors underlying the development of glaucoma in rabbits.